CONTROL OF HIGH-NONEQUILIBRIUM CONDITIONS OF ECOPROCESSES - Nikoghosyan, G.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
Based on the similarity revealed between the processes occurring in the atmosphere and in semiconductor electron-hole plasma, the issues of controlling the atmospheric conditions in the surface layer have been considered. It was established that on the analogy with multistable semiconductor electron-hole plasma a new method for monitoring the atmospheric conditions and processes taking place in the layer may be developed. Analytical expressions for the control signal and potential formed in the atmosphere of dissipative structures were obtained. These expressions were shown to serve as a sufficient basis for construction of appropriate numerical methods.
Keywords: high nonequilibrium conditions; substance distant quasicontinuous measurements; management of ecoprocesses